2016
DOI: 10.1055/s-0035-1568261
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic Effects of Alkaloids from Rhizoma Coptidis in Diet-Induced Hyperlipidemic Hamsters

Abstract: This study was conducted to evaluate the antihyperlipidemic activity of five major alkaloids in Rhizoma Coptidis using high-fat- and high-cholesterol-induced hyperlipidemic hamsters. Hyperlipidemic hamsters were treated with coptisine, berberine, jatrorrhizine, palmatine, epiberberine, and total Rhizoma Coptidis alkaloids with a dose of 46.7?mg/kg???day for 140 days. Serum total cholesterol, triglyceride, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and total bile acids were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 34 publications
1
33
0
1
Order By: Relevance
“…Modern researches have revealed that RC also exhibits hepatoprotective [15], lowering of blood cholesterol [16], antineoplastic [17] and anti-inflammatory effects [18]. Our preliminary study suggested that the hypolipidemic effects of RC alkaloids mainly attributed to the mediation of lipids metabolism related pathways in diet-induced hyperlipidemic hamsters [19]. Nevertheless, the bioavailability of RC alkaloids is below 5%, most of alkaloids are passed out of the rat body in the faeces.…”
Section: Introductionmentioning
confidence: 70%
“…Modern researches have revealed that RC also exhibits hepatoprotective [15], lowering of blood cholesterol [16], antineoplastic [17] and anti-inflammatory effects [18]. Our preliminary study suggested that the hypolipidemic effects of RC alkaloids mainly attributed to the mediation of lipids metabolism related pathways in diet-induced hyperlipidemic hamsters [19]. Nevertheless, the bioavailability of RC alkaloids is below 5%, most of alkaloids are passed out of the rat body in the faeces.…”
Section: Introductionmentioning
confidence: 70%
“…Rhizoma coptidis , commonly known as Huang Lian in China, has been one of the most important medicinal plants used for the treatment of various diseases in traditional Chinese medicine for more than 2000 years. In recent years, numerous scientific studies have demonstrated that Rhizoma coptidis and its main active constituents display a variety of activities including anti‐bacterial, anti‐cancer, anti‐hyperglycemic, anti‐hyperlipidemic, anti‐diabetic, anti‐obesity, anti‐inflammatory, radio‐protective and hepato‐protective effects . Moreover, Rhizoma coptidis and its isolated alkaloids have been reported to have cardio‐protective and neuro‐protective properties.…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin reported can decrease in cholesterol, triglycerides and LDL value with parallel increase in HDL on clinical study [23]. In vitro studies investigated the anti-hyperlipidemia effect of the alkaloid rich extract some medicinal plants [24,25]. Curcumin reported had properties to lowered oxidative damage by neutralizing free radical species when they attack the lipid membrane [26].…”
Section: Resultsmentioning
confidence: 99%